Review about School of Barbiana: Letter to a teacher - Faci Lucia, Fernando (Avances en Supervisión Educativa, 2017)
Lorenzo Milani arrived in 1954, at the age of 31, in Barbiana, a village with about 40 inhabitants, located in a poor area of the El Mugello mountains, about 45 kilometers from Florence. From the beginning he understood the importance of organizing a popular school as the only way to get children out of poverty and illiteracy. The classroom that he organized, open "twelve hours a day, 365 days a year" attended the unsuccessful students of the educational system.